An Analysis of Mother's Knowledge about the Benefits of Katuk Leaves as Food to Increase Breast Milk Production in Saba Sitahul-Tahul Village, Portibi District, North Padang Lawas Regency Year 2022 - Wulandari, Ratna (PT Inovasi Pratama Internasional, 2022)
Mother's Milk (ASI) contains many nutrients and antibodies to protect babies from infection because it is easily digested and absorbed which is beneficial for optimal growth and development for babies, even the benefits of breast milk have been proven by many researchers. One of the plants that has been traditionally used to increase and increase breast milk is katuk leaves (Sauropus androgynous (L.) Merr), the calorie, protein and carbohydrate content of katuk leaves are almost equivalent. Even the iron content of the leaves katuk is superior to papaya leaves and cassava leaves. In addition, it is also rich in vitamins A, B1 and C. Besides being rich in protein, fat, vitamins, and minerals, katuk leaves also contain tannins, saponins, and papaverine alkaloids. The type of research used is descriptive, namely knowing the mother's knowledge about the benefits of katuk leaves as a food to increase the production of breast milk (ASI). Technique taking sample on study this use Total sampling. Total population is technique taking sample where whole amount sample same with the population. So that the sample in the study This is the total population of mothers who have babies 0-12 months in Saba sitahul-tahul village in 2020 total 34 people. Based on the data analysis carried out, it is known that the majority of respondents' knowledge is in the less category, namely ( 38.2 %) in the village of Saba Sitahul-Taul in 2022. This is understandable, considering that the majority of respondents' education is in the basic education category, namely, as many as (44 , 1 %). The majority of respondents' knowledge is in the sufficient category, namely (17.6%) in Saba Sitahul Tahul village in 2022. This is understandable, considering that the majority of respondents' ages are in the 21-35 year category, namely (47.0 % ).